Oral administration of a high-branched Rhamnogalacturonan-I type pectin from Lycium barbarum regulates immune responses via small intestine-immune and colon-immune dual axis in cyclophosphamide-treated mice - Jing Lu; Jinyan Gu; Mouming Zhao; Lijun You; Lianzhu Lin (Food Bioscience, 2026)

Exercise-induced neuropeptidergic and neurochemical neuroadaptation in stress regulation and emotional disorders - Ziqi Wang; Zhinei Tan; Yaping Zhang; Yuzhou Li; Jinyan Lin; Yingli Xu; Yongxia Li; Ting Chen (Acta Neurologica Belgica, 2026)

From one base-year map to long-term paddy rice maps: an unsupervised transfer learning framework - Haoyue Jiang; Yang Zhou; Jie Song; Meng Xu; Junkai Ma; Jiaqi Song; Lin Zhu; Yanyan Shi; Jinyan Tian (International Journal of Remote Sensing, 2026)

Spatiotemporal photothermal heating and dynamic alkaline buffering work together to achieve programmable degradation of PLLA bone scaffolds - Wei Wen; Jinyan Liu; Yating Lin; Yuchen Hou; Shan Ding; Cairong Li; Yuxiao Lai; Binghong Luo (Chemical Engineering Journal, 2026)

Boosting electron transfer for high-performance microbial fuel cell with Cu2O-modified cathodes: Regulated pathway, reduced impedance, and remodelled microbial functions - Jinyan Guo; Hongxue An; Yingzhen Li; Lin Yue; Yankai Guo; Jing Lian (Bioresource Technology, 2026)

A BRIGHT platform advances integrated hazard indexing toward actionable control of human pathogenic bacteria in residential buildings - Qisheng Li; Huan Liu; Ling N. Jin; Lumeng Liu; Hua Zhou; Wenmao Zeng; Yingxian Zhai; Tian Chen; Jinyan Yu; Dongdong Su; Juan Lin; Qian Wang; et al. (Building and Environment, 2026)

A Systematic Review and Meta-analysis of Empirical Evidence for the Simple Bayesian Model of Autism - Ke Cui; Xiaoxiao Lin; Ruirui Gao; Shiqi Jing; Fei Luo; Jinyan Wang (Neuropsychology Review, 2026)

Landscape composition and soil properties shape Monolepta hieroglyphica abundance in maize field of northern China's agro-pastoral ecotone - Hainan Chong; Yinghao He; Zeyang Guo; Peng Zhang; Haikuo Zhang; Chulei Xue; Jinyan Liu; Kejian Lin; Haijun Xiao (Agriculture, Ecosystems & Environment, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Demonstration of the effective intestinal immunity activity of a high branched rhamnogalacturonan-I type pectin from wolfberry via exploration its interaction with colon biological and mechanical barrier - Jinyan Gu; Mouming Zhao; Lijun You; Lianzhu Lin (Carbohydrate Polymers, 2026)

Controls and contributions of methylotrophic methanogenesis to methane production in coastal sediments - Guang‐Chao Zhuang; Qiao Liu; Lin Yuan; Bingzheng Wu; Xiuqi Sui; Zhen Zhou; Jinyan Wang; Liang Dong; Xiting Liu; Gui‐Peng Yang; Fengping Wang (Limnology and Oceanography, 2026)
Methylotrophic methanogenesis has recently been recognized as a key process driving cryptic methane cycling within sulfate‐reducing sediments. Here we conducted biogeochemical analyses of methanogenic substrates, activity, and communities in two sediment cores (4–5 m) from the East China Sea, to constrain the dynamics and controls of methylotrophic methanogenesis in coastal sediments. We detected micromolar concentrations of methane in the presence of sulfate and high methane concentrations (up to 4.2 mM) below the sulfate–methane transition zone (~ 150–170 cm). Stable isotope composition of methane was strongly depleted (−77‰ to −91‰), indicating its biological production. Methanogenic substrates including H 2 /CO 2 , acetate, and methylated compounds were detected in the porewaters and/or sediments. Radiotracer experiments indicated methane production from various substrates, and the presence of sulfate did not inhibit methanogenesis at either site. At the coastal site with the dominance of marine organic matter (total organic carbon: 0.6%; C/N ratio: ~ 6.4; δ 13 C‐total organic carbon: −22‰), methane was primarily produced from hydrogenotrophic methanogenesis, consistent with the progressive enrichment of 13 C in dissolved inorganic carbon with depth below the sulfate–methane transition zone. However, methylotrophic methanogenesis from methanol and trimethylamine contributed significantly to methane production (up to 30.2%) at the estuarine site (total organic carbon: 0.5%; C/N ratio: 7.4, δ 13 C‐total organic carbon: −23‰) with elevated terrestrial organic matter input, also reflected from the predominance of long chain odd carbon n‐alkanes. These findings suggested that organic carbon source and composition, instead of sulfate, control methanogenic activity, providing evidence that high terrestrial organic inputs could significantly enhance methylotrophic methanogenesis in coastal sediments.

Three new compounds from Dendrobium chrysanthum Lindl. - Lin Zhao; Chao Yang; Huixia Li; Jinyan Cai (Natural Product Research, 2025)

Sub-metre surface water mapping using Sentinel-1/2 with integrated super-resolution and deep learning - Jie Song; Jinyan Tian; Lin Zhu; Bingfeng Zhou; Xinyuan Qu; Che Wang; Niu Luo; Zhenxin Zhang; Lin Guo; Mingliang Gao; Xiaojuan Li; Huili Gong (International Journal of Remote Sensing, 2025)

Biogeochemical processes play a decisive role in determining the fate of marine PAHs: A case validation with field measuring and modelling in the Beibu Gulf, South China Sea - Jingwen Shi; Mengyang Liu; Lingxin Chen; Jiandong Ye; Wupeng Xiao; Jinyan Xie; Fajin Chen; Yi-Fan Li; Xuke Chen; Yan Lin; Lin Zhang; Mingjun Feng; et al. (Journal of Hazardous Materials, 2025)

Optimizing RO membrane cleaning: A high-precision and efficient approach using electrochemical impedance spectroscopy - Jinyan Wang; Ming Gao; Manman Wang; Jingrun Xing; Dan Lu; Zhikan Yao; Lin Zhang (Desalination, 2025)

In vitro bioaccessibility of carotenoids in satsuma mandarin juice: Effects of high hydrostatic pressure and it-mediated matrix changes - Shuixian Huang; Lin Lu; Jinyan Yang; Yanbing Zhang; Xiaoyun Xu; Siyi Pan; Fengxia Liu (Food Research International, 2025)

Biofilm management via loach predation: An eco-friendly approach to enhance membrane performance in wastewater treatment - Weijia Gong; Xianwu Liu; Yuzhou Zhao; Mengmeng Jiang; Lin Guo; Le Tong; Jinyan Lu; Jiaxuan Yang; Heng Liang; Xiaobin Tang (Chemical Engineering Journal, 2025)

Identification of novel ACE inhibitory peptides from Nannochloropsis oculata through peptidomics, in silico screening and molecular docking - Liqin Lin; Wenwen Yuan; Jinyan Xiao; Jing Jia; Youping Xie; Qingyun Cai; Congjie Dai; Qingbiao Li; Baobei Wang (Food Chemistry, 2025)

Demonstration of the effective intestinal immunity activity of a high branched rhamnogalacturonan-I type pectin polysaccharide from wolfberry via exploration its interaction with mechanical barrier - Jinyan Gu; Mouming Zhao; Lijun You; Lianzhu Lin (Carbohydrate Polymers, 2025)

Marine Biogenic Volatile Organic Compounds: Production, Emission, Atmospheric Transformation, and Climate Effects - Jinyan Wang; Jianlong Li; Narcisse Tsona Tchinda; Lin Du (Current Pollution Reports, 2025)

The shrimp NF-κB pathway is activated to mediate the antioxidant defense and apoptosis under ammonia-N stress - Hongbiao Zhuo; Lanting Lin; Yuan Zhang; Shuo Fu; Jinyan Li; Xiaoxun Zhou; Guangbo Wu; Chaoan Guo; Jianyong Liu (Fish & Shellfish Immunology, 2025)

Indochina orogenic belt and related geodynamics - Wei Lin; Yin Wang; Fei Liu; Lingtong Meng; Qinying Wu; Zhao Guo; Wei Wei; Yang Chu; Jinyan Li; Qingchen Wang; Michel Faure; Vuong Van Nguyen (Science China Earth Sciences, 2025)

A comparative study of the composition of microorganisms and metabolites in different β-casein genetic types of dairy cows based on metagenomics and non-targeted metabolomics - Chuanchuan Wang; Jinyan Zhao; Wei Zhao; Lin Xue; Yafei Chen; Jia Tian; Hua Wang; Xiaoyun Ji; Xiaohua Tian; Juan Zhang; Yaling Gu (Food Research International, 2025)

National scale sub-meter mangrove mapping using an augmented border training sample method - Jinyan Tian; Le Wang; Chunyuan Diao; Yameng Zhang; Mingming Jia; Lin Zhu; Meng Xu; Xiaojuan Li; Huili Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

CLSSATP: Contrastive learning and self-supervised learning model for aquatic toxicity prediction - Ye Lin; Xin Yang; Mingxuan Zhang; Jinyan Cheng; Hai Lin; Qi Zhao (Aquatic Toxicology, 2025)

Characterization of newly isolated Bacillus cereus D3 Co-producing α-amylase and protease and its application in food raw materials - Shuang Wang; Hua Bai; Zongmin Wang; Lin Peng; Ling Li; Hongbo Yan; Lanlan Zhu; Yanbo Wang; Jinyan Shao; Jizhou Liu (Food Bioscience, 2024)

Microbial community succession and changes of volatile compounds in the fermentation process of bamboo shoots - Jinmei Wei; Zongjun Li; Jinyan Kuang; Zikang Yan; Li Wang; Ying Lin; Jin Du; Ke Li; Yuanliang Wang; Li Yang (Food Microbiology, 2024)

Effects of ammonia exposure and post-exposure recovery in pacific white shrimp, Litopenaeus vannamei: Histological, physiological and molecular responses - Lanting Lin; Hongbiao Zhuo; Yuan Zhang; Jinyan Li; Xiaoxun Zhou; Guangbo Wu; Chaoan Guo; Jianyong Liu (Aquatic Toxicology, 2024)

Integrated physiological, metabolome, and transcriptome analysis of the hepatopancreas in Penaeus vannamei under ammonia stress - Jinyan Li; Lanting Lin; Hongbiao Zhuo; Yuan Zhang; Jianyong Liu; Xiaoxun Zhou; GuangBo Wu; Chaoan Guo (Aquaculture International, 2024)

A Spatial–Temporal Analysis and Multi-Scenario Projections of Carbon Sequestration in Sea Islands: A Case Study of Pingtan Island - Siyu Chen; Ming Xu; Heshan Lin; Fei Tang; Jinyan Xu; Yikang Gao; Yunling Zhuang; Yong Chen (Journal of Marine Science and Engineering, 2024)
As an indispensable part of the marine ecosystem, the health status of the sea affects the stability and enhancement of the overall ecological function of the ocean. Clarifying the future land and sea utilization pattern and the impacts on the carbon stocks of island ecosystems is of great scientific value for maintaining marine ecological balance and promoting the sustainable development of the island ecosystem. Using Pingtan Island as an example, we simulate and predict changes in island utilization and carbon stocks for historical periods and multiple scenarios in 2030 via the PLUS-InVEST model and the marine biological carbon sink accounting method. The results show that (1) from 2006 to 2022, the carbon stock of Pingtan Island decreased by 7.218 × 104 t, resulting in a cumulative economic loss of approximately USD 13.35 million; furthermore, from 2014 to 2018, the implementation of many reclamation and land reclamation projects led to a severe carbon stock loss of 6.634 × 104 t. (2) By 2030, the projected carbon stock under the three different policy scenarios will be greater than that in 2022. The highest carbon stock of 595.373 × 104 t will be found in the ecological protection scenario (EPS), which will be 4.270 × 104 t more than that in 2022. With the strong carbon sequestration effect of the ocean, the total social carbon cost due to changes in island utilization is projected to decrease in 2030. (3) The factors driving changes in island utilization will vary in the design of different future scenarios. The results of this study not only provide a solid scientific basis for the sustainable development of island areas, but they also highlight the unique contribution of islands in the field of marine ecological conservation and carbon management, contributing to the realization of the dual-carbon goal.

CO2 retention in high-pressure/high-temperature reservoirs of the Yinggehai Basin, northwestern South China Sea - Jinyan Lin; Rui Liu; Niklas Heinemann; Johannes M. Miocic; Jinqiang Tian; Zengyu Chen; Lin Hu; Yazhen Zhang; Julien Amalberti; Lichao Wang (International Journal of Greenhouse Gas Control, 2024)

Ovalbumin promotes innate immune response of Caenorhabditis elegans through DAF-16 and SKN-1 pathways in insulin/IGF-1 signaling - Haibing Pei; Zhiyin Lin; Kexin Yao; Yeqing Luo; Ping Tong; Hongbing Chen; Yong Wu; Zhihua Wu; Jinyan Gao (Journal of Physiology and Biochemistry, 2024)

TAG encodes an adenine nucleotide transport protein that regulates leaf color in rice - Xinfang Zhang; Wenwen Xiao; Mi Wei; Ruhui Wu; Jinyan Liu; Jing You; Jianyan Mu; Jichao Zhang; Yanling Yang; Yitao Wan; Yinghua Lin; Guanghua He; et al. (Euphytica, 2024)

Remodeling of central carbon metabolism of Nannochloropsis oceanica in response to gradual nitrogen depletion - Baobei Wang; Yayun Xu; Liqin Lin; Jinyan Xiao; Youping Xie; Congjie Dai; Jing Jia (Algal Research, 2024)

Annual mapping of Spartina alterniflora with deep learning and spectral-phenological features from 2017 to 2021 in the mainland of China - Xiarong Li; Jinyan Tian; Xiaojuan Li; Yongxin Yu; Yang Ou; Lin Zhu; Xiumin Zhu; Bingfeng Zhou; Huili Gong (International Journal of Remote Sensing, 2024)

Stenotrophomonas maltophilia contributes to smoking-related emphysema through IRF1-triggered PANoptosis of alveolar epithelial cells - Haibo Xia; Jiaheng Lin; Yue Wang; Jinyan Yu; Hailan Wang; Cheng Cheng; Yi Yang; Tao Bian; Yan Wu; Qizhan Liu (Environmental Pollution, 2024)

Demonstration of feasibility and effectiveness of deep eutectic solvent-water system extraction of RG-I type pectin from wolfberry based on target polysaccharide, solvent and their interactions - Jinyan Gu; Lianzhu Lin; Mouming Zhao (Food Hydrocolloids, 2023)

Improved ammonia emission inventory of fertilizer application for three major crops in China based on phenological data - Yongqi Zhao; Baojie Li; Jinyan Dong; Yan Li; Xueqing Wang; Cong Gan; Yingzhen Lin; Hong Liao (Science of The Total Environment, 2023)

How to extend the lifetime of RO membrane? From the perspective of the end-of-life RO membrane autopsy - Jinyan Wang; Jingrun Xing; Ge Li; Zhikan Yao; Zhen Ni; Jing Wang; Songmiao Liang; Zhijun Zhou; Lin Zhang (Desalination, 2023)

GS6.1 controls kernel size and plant architecture in rice - Hongyuan Zhao; Yu Fu; Guiquan Zhang; Yingqin Luo; Weifeng Yang; Xiaoya Liang; Lin Yin; Zhenwu Zheng; Yijun Wang; Zhan Li; Haitao Zhu; Jinyan Huang; et al. (Planta, 2023)

Neoproterozoic Diamictite of the Luoquan Formation from the North China Block and Their Implications - Peishan Sui; Weidong Sun; Nan Han; Lei Wang; Shiwen Xie; Zihang Huang; Xiaohong Wang; Hongmei Gong; Jin Liu; Jinyan Lin; Yuanyuan Xiao (Journal of Earth Science, 2023)

Mixed exposure effect of seminal metals on semen quality, mediation of total antioxidant capacity, and moderation of GSTM1/GSTT1 gene deletion in Chinese reproductive-aged men - Jingchao Ren; Huidong Jin; Chen Zhang; Song Liu; Yufen Han; Jinyan Xi; Jinhu Cao; Fenglong Lin; Pingyang Zhang; Fengquan Zhang; Guang-hui Zhang; Huijun Yang; et al. (Environmental Research, 2023)

New evidence of the Hoyle-like structure in 16O - Jiahao Chen; Yanlin Ye; Kai Ma; Jiaxing Han; Dongxi Wang; Chengjian Lin; Huiming Jia; Lei Yang; Gen Li; Lisheng Yang; Ziyao Hu; Zhiwei Tan; et al. (Science Bulletin, 2023)

Identification of Hub Genes Associated with Abnormal Endothelial Function in Early Coronary Atherosclerosis - Xue Qiu; Jinyan Lin; Yanbing Chen; Bixiao Liang; Lang Li (Biochemical Genetics, 2022)

Ergosterol peroxide: an effect-directed detecting method from Anoectochilus elwesii and evaluation of anticancer activity - Yanduan Lin; Bingqin Wen; Ziwei Zhang; Jinyan Cai (Natural Product Research, 2022)

Hasubanan alkaloids with anti-inflammatory activity from Stephania longa - Hui Liu; Wan-Qin Liao; Rong-Xiao Lin; Lixia Fan; Jinyan Sun; Hong-Yuan Chen; Fang Liu; An-Ping Yang (Natural Product Research, 2022)

The coupling relationship between urbanization and ecological resilience in the Pearl River Delta - Shaojian Wang; Zitian Cui; Jingjie Lin; Jinyan Xie; Kun Su (Journal of Geographical Sciences, 2022)

Sand barrier morphological evolution based on time series remote sensing images: a case study of Anhaiao, Pingtan - Heshan Lin; Xingguang Yu; Zhigang Yu; Yikang Gao; Jinyan Xu; Aiping Feng; Zhijun Liu; Degang Jiang; Fan Yu (Acta Oceanologica Sinica, 2020)

Transcriptome sequencing of Eospalax fontanierii to determine hypoxia regulation of cardiac fibrinogen - Lulu Xu; Zhiqiang Hao; Jinyan Lin; Qiong Zhao; Baojun Zhang; Guanglin Li; Jianping He; Jingang Li (Molecular Biology Reports, 2019)

A new furostanol saponin from Dendrobium chrysanthum Lindl. with cytotoxic activity - Chao Yang; Weilong Lin; Lin Zhao; Jinyan Cai (Natural Product Research, 2019)

Identification of novel miRNAs and their target genes in Eucalyptus grandis - Zheng Lin; Qingfen Li; Qi Yin; Jinyan Wang; Baolong Zhang; Siming Gan; Ai-Min Wu (Tree Genetics & Genomes, 2018)

Detection of new phenylpropanoids from Dendrobium chrysanthum - Jinyan Cai; Chao Yang; Tianhong Chen; Lin Zhao (Natural Product Research, 2018)

The climatic impacts of land use and land cover change compared among countries - Jiyuan Liu; Quanqin Shao; Xiaodong Yan; Jiangwen Fan; Jinyan Zhan; Xiangzheng Deng; Wenhui Kuang; Lin Huang (Journal of Geographical Sciences, 2016)

A new flavonol triglycoside derived from Anoectochilus elwesii on stimulating glucose uptake in insulin-induced human HepG2 cells - Jinyan Cai; Lin Zhao; En Zhu (Natural Product Research, 2015)

Stimulating effect of a new triterpene derived from Anoectochilus elwesii on glucose uptake in insulin-resistant human HepG2 cells - Jinyan Cai; Lin Zhao; En Zhu; Jiao Guo (Natural Product Research, 2014)

An equilibrium analysis of the land use structure in the Yunnan Province, China - Jiao Luo; Jinyan Zhan; Yingzhi Lin; Chunhong Zhao (Frontiers of Earth Science, 2014)

An equilibrium analysis of the land use structure in the Yunnan Province, China - Jiao Luo; Jinyan Zhan; Yingzhi Lin; Chunhong Zhao (Frontiers of Earth Science, 2014)

Simulation on the dynamics of forest area changes in Northeast China - Xiangzheng Deng; Qun’ou Jiang; Jinyan Zhan; Shujin He; Yingzhi Lin (Journal of Geographical Sciences, 2010)

Factors and mechanism driving the land-use conversion in Jiangxi Province - Jinyan Zhan; Nana Shi; Shujin He; Yingzhi Lin (Journal of Geographical Sciences, 2010)